Optimized method for black carbon analysis in ice and snow using the Single Particle Soot Photometer - I. A. Wendl; J. A. Menking; R. Färber; M. Gysel; S. D. Kaspari; M. J. G. Laborde; M. Schwikowski (Atmospheric Measurement Techniques, 2014)
In this study we attempt to optimize the method for measuring black carbon (BC) in snow and ice using a Single Particle Soot Photometer (SP2). Beside the previously applied ultrasonic (CETAC) and Collison-type nebulizers we introduce a jet (Apex Q) nebulizer to aerosolize the aqueous sample for SP2 analysis. Both CETAC and Apex Q require small sample volumes (a few milliliters) which makes them suitable for ice core analysis. The Apex Q shows the least size-dependent nebulizing efficiency in the BC particle diameter range of 100–1000 nm. The CETAC has the advantage that air and liquid flows can be monitored continuously. All nebulizer-types require a calibration with BC standards for the determination of the BC mass concentration in unknown aqueous samples. We found Aquadag to be a suitable material for preparing calibration standards. Further, we studied the influence of different treatments for fresh discrete snow and ice samples as well as the effect of storage. The results show that samples are best kept frozen until analysis. Once melted, they should be sonicated for 25 min, immediately analyzed while being stirred and not be refrozen.